2019
DOI: 10.1111/tbed.13144
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and evolution of countries affected by bovine brucellosis (1996–2014)

Abstract: This paper describes the global distribution and temporal evolution of bovine brucellosis due to Brucella abortus during a 19‐year period (1996–2014) using the information officially reported to the World Organisation for Animal Health (OIE) by veterinary services of 156 countries. Variables that can influence the health status of bovine brucellosis (i.e., year, per capita Gross Domestic Product (GDP), continent and bovine population) were also analysed. Countries were classified into three categories of healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
0
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 46 publications
1
33
0
8
Order By: Relevance
“…Our research showed that in China, the distribution of regions with high incidence of HB had almost no overlap with the distribution of high levels of per capita GDP. This was consistent with the conclusions of many previous studies [15,21]. A global study showed that countries with relatively high per capita GDP tend to have less brucellosis; another study showed that rainfall and per capita GDP in China's temperate regions are low and negatively related to the number of cattle and sheep.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our research showed that in China, the distribution of regions with high incidence of HB had almost no overlap with the distribution of high levels of per capita GDP. This was consistent with the conclusions of many previous studies [15,21]. A global study showed that countries with relatively high per capita GDP tend to have less brucellosis; another study showed that rainfall and per capita GDP in China's temperate regions are low and negatively related to the number of cattle and sheep.…”
Section: Discussionsupporting
confidence: 91%
“…In previous studies, a clear relationship between economic resources and health status has been observed across multiple countries, where developing countries with fewer resources are more susceptible to infections [15]. At present, many studies have demonstrated the relationship between per capita gross domestic product (GDP) and the incidence of Class B infectious diseases in China.…”
Section: Introductionmentioning
confidence: 99%
“…It has been indicated that changing socio-economic conditions, such as increasing population densities in urban areas and increasing GDPs, may be correlated with the possibility of infection emergence and transmission [13]. Countries with relatively high GDP are normally brucellosis-free [25]. Densely populated areas and areas with poor sanitation and hygiene contribute to the spread of foodborne and soil-borne diseases [26].…”
Section: Discussionmentioning
confidence: 99%
“…In low to middle income countries such as CR, brucellosis is a persistent disease in domestic animals that endures due to local farming practices and the easy movement of animals across borders [52]. This movement of animals or their products, allows the dispersion of infectious agents such as Brucella spp.…”
Section: Discussionmentioning
confidence: 99%